Study on the cut-off point and the influencing factors of distress in newly diagnosed breast cancer patients - Liu, Ling; Wang, Rong; Sun, Yiming; Xiao, Ying; Du, Guangsheng; Zhang, Qingling (Frontiers in Psychology, 2024)
Objective: Our aim is to investigate the cut-off point of distress and the influencing factors associated with distress in patients with newly diagnosed breast cancer. Methods: A cross-sectional survey of distress was conducted in 167 patients with newly diagnosed breast cancer admitted to the Department of General Surgery of a tertiary care hospital from July 2020 to March 2022 .Patients completed the Hospital Anxiety and Depression Scale (HADS) and the Distress Thermometer (DT) questionnaire within 3 days of admission.The HADS ≥ 15 was used as the gold standard, and the cut-off point of the DT measure was analyzed using the Receiver Operating Characteristi (ROC) curve. The cut-off point obtained by ROC curve analysis was used to analyze the influencing factors of distress in breast cancer patients by univariate and multivariate regression analysis. Results:A total of 167 patients completed the survey, with an average HADS score of 8.43±5.84 and a total HADS score of ≥15 in 37 (22.16%) patients，the mean DT score was 2.96 ± 1.85。 ROC curve analysis showed an area under the curve of 0.885, with a maximum Jorden index (0.723) at a DT score of 4,the sensitivity was 100.0% and specificity was 72.3%. There were 73 (43.71%) patients with DT score≥4.Regression analysis showed that insurance/financial problems, dealing with partner problems, tension, bathing/dressing problems, pain, and sleep problems were independent risk factors for l distress in newly diagnosed breast cancer patients. Conclusion:A DT score 4 is the cut-off point for distress in patients with newly diagnosed breast cancer. In clinical practice, target intervention should be carried out according to the risk factors of distress of patients.